The Assyrian Dictionary of the Oriental Institute of the University of Chicago. Vol. 2: В (1965)
Editorial Board: Ignace J. Gelb, Benno Landsberger, A. Leo Oppenheim, Erica Reiner. Vol. 2: В (A. Leo Oppenheim, Editor-in Charge; Erica Reiner, Editor; Robert D. Biggs, Associate Editor; with the assistance of John A. Brinkman, Michael B. Rowton, Aaron Shaffer, and Ronald F. G. Sweet; Assistant to the Editors: Jean Eckenfels); DM 88.